The Energy Potential of Harvested Wood Fuel by Refugees in Northern Uganda - Bernard Barasa; Loy Turyabanawe; Gertrude Akello; Paul Makoba Gudoyi; Claire Nabatta; Andrew Mulabbi (The Scientific World Journal)
For the last three decades, Uganda has lost considerable natural vegetation cover in the refugee settlements and buffer zones due to the high demand for wood fuel and timber. It is worthy to note that the supplies of wood fuel are more likely to dwindle in the near future. This study explored the determinants of harvested wood-fuel choices and their energy potential. It also examined the implemented energy conservation measures and constraints faced by the refugees both in Palorinya and Imvepi refugee settlements in Northern Uganda. The data were collected by conducting household interviews and collection of wood species samples for energy potential laboratory analysis. Findings indicate that the major sources of wood fuel were firewood, charcoal, briquettes, and biomass fuels. The major refugee choices that determined wood-fuel collection included the family size of the house hold, culture, method of cooking, type of food cooked, high poverty levels, and availability of family labour (P≤0.05). The sampled wood tree species had the highest energy potential were Celtis durandii (5,837 kcal/kg), Parkinsonia aculeata (5,771 kcal/kg), Delonix regia (5,153 kcal/kg), and Bligihia unijugata (5,034 kcal/kg). Access to wood fuel by the households was mainly constrained by limited household income levels, long distances trekked, and inadequate awareness about wood fuel sources and availability. To conserve wood fuel, the refugees deploy several measures including the use of mobile solar gadgets for cooking and lighting, taking up agroforestry, use of briquettes, adoption of energy-saving cooking stoves, and establishment of new woodlots. Therefore, to reverse this trend, the Ugandan government and development partners should prioritise energy investments by supporting cheaper energy alternatives such as mobile solar gadgets and energy-saving cooking technologies, and establishment of woodlots.